Fecal Microbial Transplantation in Critically Ill Patients-Structured Review and Perspectives - Cibulková, Ivana; Řehořová, Veronika; Hajer, Jan; Duška, František (Biomolecules, 2021)
The human gut microbiota consists of bacteria, archaea, fungi, and viruses. It is a dynamic ecosystem shaped by several factors that play an essential role in both healthy and diseased states of humans. A disturbance of the gut microbiota, also termed "dysbiosis", is associated with increased host susceptibility to a range of diseases. Because of splanchnic ischemia, exposure to antibiotics, and/or the underlying disease, critically ill patients loose 90% of the commensal organisms in their gut within hours after the insult. This is followed by a rapid overgrowth of potentially pathogenic and pro-inflammatory bacteria that alter metabolic, immune, and even neurocognitive functions and that turn the gut into the driver of systemic inflammation and multiorgan failure. Indeed, restoring healthy microbiota by means of fecal microbiota transplantation (FMT) in the critically ill is an attractive and plausible concept in intensive care. Nonetheless, available data from controlled studies are limited to probiotics and FMT for severe C. difficile infection or severe inflammatory bowel disease. Case series and observational trials have generated hypotheses that FMT might be feasible and safe in immunocompromised patients, refractory sepsis, or severe antibiotic-associated diarrhea in ICU. There is a burning need to test these hypotheses in randomized controlled trials powered for the determination of patient-centered outcomes.
Keywords: critically ill; fecal microbial transplantation; feces; Feces; kritický stav; Gastrointestinal Microbiome; Inflammatory Bowel Diseases; lidé; průjem; fekální transplantace; Fecal Microbiota Transplantation; Dysbiosis; střevní mikroflóra; Diarrhea; dysbióza; multiorgan failure; gut microbiota; idiopatické střevní záněty; Critical Illness; Humans